Plasma Rich in Growth Factors Promotes Autophagy in ARPE19 Cells in Response to Oxidative Stress Induced by Blue Light - Carlota Suárez-Barrio; Susana del Olmo-Aguado; Eva García-Pérez; Luis Fernández-Vega-Cueto; Andrés Fernández-Vega Cueto; Begoña Baamonde-Arbaiza; Luis Fernández-Vega; Jesús Merayo-Lloves (Biomolecules, 2021)
Age-related macular degeneration (AMD) causes the degeneration of photoreceptors and retinal cells leading to vision loss in older subjects. Among possible exogenous risk factors, it has been recently proposed that long-term exposure to blue light could aggravate the course of AMD. In the search for therapeutic options, plasma rich in growth factors (PRGF) has been shown to enhance cell antioxidant pathways and protect photoreceptors against the harm produced by blue light, although its mechanism of action remains unknown. One possible mechanism, autophagy, is one of the most conservative cell renewal systems used in eukaryotes to destroy cellular components that have been damaged by some kind of insult. The oxidative stress of exposure to blue light is known to induce cell autophagy. In this study, we examined the combined effects on autophagy of blue light and PRGF in a retinal cell line, ARPE19. In response to treatment with both PRGF and blue light, we detected the modulated expression of autophagy markers such as NF-kB, p62/sqstm1, Atg5, LC3 and Beclin1, and inflammatory markers such as IL1B and IL18. Our findings suggest that PRGF promotes cell autophagy in response to exposure to blue light.